The role of work overload on turnover intention and job stress as an intervening variable in gen Z employees in Pontianak City - Orianhoi, Albertus Leodesto; Ginting, Sunardi (International Journal of Enterprise Modelling, 2025)
The phenomenon of high turnover intention in a competitive work environment is a significant challenge for organizations, especially when work overload and job stress become dominant factors that influence employees' decisions to leave their jobs. This study aims to analyze the direct and indirect effects of work overload on turnover intention through the mediation of job stress. Using a quantitative approach, data was collected through a survey of 250 respondents from various industrial sectors in urban Indonesia, and analyzed using structural equation modeling (SEM) techniques. The results showed that work overload has a positive and significant influence on job stress and turnover intention, with job stress acting as a partial mediator in the relationship. The practical implications of these findings indicate the importance of organizations in managing employee workload and creating a supportive work environment to reduce job stress and improve employee retention. This study has limitations in geographically and sectorally limited sample coverage, so further studies with a more comprehensive approach are proposed to strengthen the generalizability of the results as well as explore other factors that may moderate the relationship between variables.